Vocal and self-perception effects of straw phonation exercises - Larissa Rezende da Paixão; Márcia Cristina Bebiano Tannes; Bárbara Oliveira Souza; Lorena Luiza Costa Rosa Nogueira; Renata Maria Moreira Moraes Furlan (Revista CEFAC, 2021)
ABSTRACT Purpose: to assess the acoustic and self-perceived voice changes in women with and without voice symptoms after 1, 3, 5, and 7 minutes of straw phonation exercises. Methods: a total of 30 women aged 18 to 39 years participated in the study - 17 with and 13 without voice symptoms. The participants filled in the visual analog scale on self-perceived voice discomfort. The sustained vowel /ɛ/ was recorded in maximum phonation time before (m0) and after the first, third, fifth, and seventh minute performing straw phonation exercises. The maximum phonation time was measured, and an acoustic analysis was made, encompassing the following parameters: the number of harmonics, fundamental frequency, noise, glottal-to-noise excitation ratio (GNE), jitter, and shimmer. The Friedman and Wilcoxon tests were used to compare each parameter at the different moments, and the Mann-Whitney test, to compare the groups. The 5% significance level was set for the analyses. Results: no changes were found in either the acoustic variables or the self-perception of voice comparing the moments before and after the exercises in either group. The comparison between the groups revealed that the one with voice symptoms had lower GNE and higher noise values at the second moment performing the technique. Conclusion: the straw phonation did not cause acoustic or self-perceived voice changes in women with and without voice symptoms. The comparison between the groups showed that the women with symptoms had lower GNE and higher noise values than those without symptoms, after 1 minute performing straw phonation.